أثر برنامج الإصلاح الاقتصادي في الاختلالات الهيكلية للاقتصاد السوري - قنوع نزار; عباس غادة; لايقة رامي كاسر (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يناقش البحث أثر الإصلاح الاقتصادي في الاختلالات الهيكلية التي يعاني منها الاقتصاد السوري، وذلك من خلال دراسة أهم مظاهر الاختلال الهيكلي وتحليلها في الاقتصاد السوري المتمثلة باختلالين رئيسين: الاول: هو اختلال هيكل الموارد الاقتصادية الذي يتمحور بصورة رئيسية حول ثلاث فجوات هي: الفجوة بين الادخار والاستثمار(فجوة الموارد الداخلية) والفجوة بين الصادرات والمستوردات (فجوة الموارد الخارجية) والفجوة بين الإيرادات والنفقات(فجوة الموازنة العامة) والثاني هو اختلال هيكل الإنتاج، وصولاً إلى تحديد النتائج ووضع بعض المقترحات التي تفيد في معالجة هذه الاختلالات الهيكلية وبالتالي إعادة حالة التوازن العام للاقتصاد السوري. The search discusses the impact of economic reform on the structural imbalances of the Syrian economy through studying and analyzing the most important manifestations of structural imbalance in the Syrian economy of major disorders: the first is the disruption of the structure of economic resources centered mainly around three gaps: the gap between savings and investment (internal resource gap), the gap between exports and imports (external resource gap), and the gap between revenues and expenditures (general budget gap); the second is the disruption of the production structure in order to determine the results and put together some proposals that address these structural imbalances and restoring equilibrium to the Syrian economy.